Mathematics higher level topic 7 - option : statistics and probability for the IB diploma - Fannon, Paul, author (Cambridge : Cambridge University Press, 2013)
This title forms part of the completely new Mathematics for the IB Diploma series. This highly illustrated book covers topic 7 of the IB Diploma Higher Level Mathematics syllabus, the optional topic Statistics and Probability. It is also for use with the further mathematics course. Based on the new group 5 aims, the progressive approach encourages cumulative learning. Features include: a dedicated chapter exclusively for mixed examination practice; plenty of worked examples; questions colour-coded according to grade; exam-style questions; feature boxes throughout of exam hints and tips and calculator skills sheets to support students in using their Casio or Texas calculators.